2010
DOI: 10.1007/s00381-010-1368-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and functional outcome in spina bifida–Chiari II malformation

Abstract: Despite intervention in childhood and adequate cerebrospinal fluid diversion the prognosis for independent living into adulthood remains poor. All patients have elements of cognitive impairment. Structural brain abnormalities may be more important determinants of cognitive outcome than shunt malfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…These studies suggest that physical problems may negatively affect physicosocial status. Some studies showed lower scores in the physical domain of the HRQOL measure in individuals with SB in comparison to healthy children (31)(32)(33). At the end of our study, we observed that there was no improvement in sphincter control, mobility, transfers, and other physical function problems with increasing age, but there was significant progress in the SE, REB, BE, and MH sub-scales.…”
Section: Discussionsupporting
confidence: 41%
“…These studies suggest that physical problems may negatively affect physicosocial status. Some studies showed lower scores in the physical domain of the HRQOL measure in individuals with SB in comparison to healthy children (31)(32)(33). At the end of our study, we observed that there was no improvement in sphincter control, mobility, transfers, and other physical function problems with increasing age, but there was significant progress in the SE, REB, BE, and MH sub-scales.…”
Section: Discussionsupporting
confidence: 41%
“…Furthermore, our previous study only showed association with continence to shunt and level of the lesion; effect on QoL was not investigated. The significant physical impairment associated with spina bifida, hydrocephalus and shunts is often associated with cognitive defects and learning disabilities (24,25). This has been extrapolated to suggest that these patients are less 'bothered' by their incontinence (20).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our small adult follow-up sample, parent-and self-reports continued to result in higher T-score means (relative to normative values), suggesting persistence of some aspects of executive dysfunction as youth with MMH transition into adulthood. These findings thus have relevance for transition-aged youth with MMH, particularly within the context of other research suggesting persisting learning and cognitive deficits into adulthood (Jenkinson et al, 2011). We have proposed that, when combined with other cognitive and psychosocial variables, executive dysfunction may further detract from the ability of young adults to become independent in managing aspects of their own self-care and medical self-management (Tarazi et al, 2007).…”
Section: Discussionmentioning
confidence: 87%